A study on conservation of architectural elements on the old mosque / Noor Shidah Ibrahim - Ibrahim, Noor Shidah (2012)
This research is generally a study about the old mosque architectural elements in Melaka. Masjid Al-Kauthar, Masjid Al-Khairiyah, Masjid An-Nur and Masjid Pekan are selected as the case study because the mosque is the oldest mosque in Melaka and it has the identity by itself. This mosque had been gazette by PERZIM base on two criteria, first is the mosque still has the origin characteristics base on the design although the mosque had any renovation or extension. Second criteria are the roof and also the “tiang seri” column. For the architectural elements of old mosque in Melaka, it will discuss the specific architectural elements such as mihrab, minbar, minaret, dome, ablution area and cemetery and others architectural elements such as roof, columns, wall, floor and openings. All old mosque in Melaka is basically has the similarity to each other and the unique of this old mosque is the architectural features although it is in different district. The different of old mosque architecture in Melaka compared to the mosque in other states are the roof design, tower (minaret) and also the “tiang seri” column as a supported.